A frente nacional e os limites à democracia na Colômbia (1958-1974) - Silva, Ana Carolina Silva Ramos e (2011)
This study examines the role of political institutions in Colombia during the term of the National Front (1958-1974) - a coalition government composed of the Liberal and Conservative parties - in order to assess whether the model of democracy in the country walked towards democratic openness, according to the arguments of authors such as Pécaut (2010) and Dahl (2005), or a particular type called democracia restringida, as advocated by Jimenez (2009). This analysis is considered an important explanatory variable regarding the origin and permanence of the armed conflict in Colombia. Thus, during the research a fundamental tool for the analysis of political institutions were the Colombian electoral data, which allowed us to evaluate the degree of consensus, reached by the presidents of the National Front with civil society. Another fact of great importance was the analysis of systematic state of emergency declarations in the country, which ultimately demonstrated the need for the state to use repressive methods in order to impose its domination on the opposition. Finally the study analyses how the arbitrary methods used by governments to keep the coalition government in power reflected in the organizational model of the protest movement whose radicalization of many of them culminated in the Colombian guerrillas that persist until nowadays.